The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1128/mcb.18.11.6305
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptor, C/EBP, HNF3, and Protein Kinase A Coordinately Activate the Glucocorticoid Response Unit of the Carbamoylphosphate Synthetase I Gene

Abstract: A single far-upstream enhancer is sufficient to confer hepatocyte-specific, glucocorticoid-and cyclic AMPinducible periportal expression to the carbamoylphosphate synthetase I (CPS) gene. To identify the mechanism of hormone-dependent activation, the composition and function of the enhancer have been analyzed. DNase I protection and gel mobility shift assays revealed the presence of a cyclic AMP response element, a glucocorticoid response element (GRE), and several sites for the liver-enriched transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 78 publications
(107 reference statements)
3
77
0
Order By: Relevance
“…11 Previous studies [12][13][14][15] have shown that CPS1 transcription is subject to physiological regulation and that CPS1 activity can be inhibited by a hepatotoxic dose of acetaminophen. Studies 16,17 have also suggested that an 80-bp glucocorticoid response unit located 6.3 kb upstream of the transcription start site mediates hormone responsiveness and liver-specific expression of CPS1 in rats. A recent study 18 revealed that Y-box binding protein-1 negatively regulates CPS1 expression via suppression of CCAAT enhancer-binding protein-␣ function in fetal and injured adult mouse liver but not in normal adult liver.…”
mentioning
confidence: 99%
“…11 Previous studies [12][13][14][15] have shown that CPS1 transcription is subject to physiological regulation and that CPS1 activity can be inhibited by a hepatotoxic dose of acetaminophen. Studies 16,17 have also suggested that an 80-bp glucocorticoid response unit located 6.3 kb upstream of the transcription start site mediates hormone responsiveness and liver-specific expression of CPS1 in rats. A recent study 18 revealed that Y-box binding protein-1 negatively regulates CPS1 expression via suppression of CCAAT enhancer-binding protein-␣ function in fetal and injured adult mouse liver but not in normal adult liver.…”
mentioning
confidence: 99%
“…20). Mutation of the C/EBP, HNF3, or GR recognition site within this unit almost completely abolishes the hormonal response, showing the strict requirement of the intact GRU for such a response (20).…”
Section: The Interaction Between the Upstream Regulatory Fragment Andmentioning
confidence: 96%
“…The promoter of construct 4 extends from Ϫ38 to ϩ138, that is, additionally lacks the GAG box (19,25). Constructs 5-7 are comparable with constructs 2-4, respectively, except that the URF is replaced by the 102-bp GRU fragment (20). * The costs of publication of this article were defrayed in part by the payment of page charges.…”
Section: Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations